BATF sustains homeostasis and functionality of bone marrow Treg cells to preserve homeostatic regulation of hematopoiesis and development of B cells - Tikka, Chiranjeevi; Beasley, Lindsay; Xu, Chengxian; Yang, Jing; Cooper, Scott; Lechner, Joseph; Gutch, Sarah; Kaplan, Mark H.; Capitano, Maegan; Yang, Kai (Frontiers in Immunology, 2023)
Bone marrow Treg cells (BM Tregs) orchestrate stem cell niches crucial for hematopoiesis. Yet little is known about the molecular mechanisms governing BM Treg homeostasis and function. Here we report that the transcription factor BATF maintains homeostasis and functionality of BM Tregs to facilitate homeostatic regulation of hematopoiesis and B cell development. Treg-specific ablation of BATF profoundly compromised proportions of BM Tregs associated with reduced expression of Treg effector molecules, including CD44, ICOS, KLRG1, and TIGIT. Moreover, BATF deficiency in Tregs led to increased numbers of HSCs, multipotent progenitors, and granulocyte-macrophage progenitors (GMPs), while reducing the functionality of myeloid progenitors ex vivo and the generation of common lymphoid progenitors. Furthermore, Tregs lacking BATF failed to support the development of B cells in the BM. Mechanistically, BATF mediated IL-7 signaling to promote expression of effector molecules on BM Tregs and their homeostasis. Our studies reveal a previously unappreciated role for BATF in sustaining BM Treg homeostasis and function to ensure hematopoiesis.